Design and Implementation Model for Linearization Sensor Characteristic by FPAA - Salman, Alaa Abdul Hussein; Tahir, Fadhil Rahma; Rashid, Mofeed Turky (Iraqi Journal for Electrical and Electronic Engineering, 2015)
Linearization sensors characteristics becomes very interest field for researchers due to the importance in enhance the system performance, measurement accuracy, system design simplicity (hardware and software), reduce system cost, ..etc. in this paper, two approaches has been introduced in order to linearize the sensor characteristics; first is signal condition circuit based on lock up table (LUT) which this method performed for linearize NTC sensor characteristic. Second is ratiometric measurement equation which this method performed for linearize LVDT sensor characteristic. The proposed methods has been simulated by MATLAB, and then implemented by using Anadigm AN221E04 Field Programmable Analog Array (FPAA) development kit which several experiments performed in order to improve the performance of these approaches.